L’ Espagne au Maroc et la question de Tanger : la trajectoire erratique d’une ville portuaire dans les relations internationales (1500-1940) - Daha Cherif, Ba (Études sur la Région Méditerranéenne, 2010)
Tangiers was the battlefield of the Mediterranean powers: England, Germany, Belgium, France, Spain and Italy. Spain took two important decisions for Morocco. For the Sultan of Morocco, the Spanish troops firmly committed themselves by the Algesiras Act of 1906, to quell the Rif rebellion and rule in his name, the Spanish influence zone. The 1921 rout will be harshly sanctioned. In fact, Spain renounced to the mission that consisted in pacifying Northern Morocco in the name of the Sultan by instituting his religious authority and the political statutes which was laboriously elaborated has been destroyed. And Their Catholic Majesties made the firm promise to the Spanish people to keep the city of Tangiers as part of their colonial possessions throughout the World in general and in North Africa in particular. Not only did Spain record a dismal failure to the Rif troops commanded by the uncompromising figure of Abdel Krim who held the "Republic of Rif " project and caused heavy losses, trough about humiliation and disgrace felt even in the streets of Madrid and Barcelona. Henceforth, they were vexed and concerned with the interminable trials of "Generals who betrayed the Spanish nation ". It should also be noted that following the Anoual disasters of 1920, General Primo de Rivera was mobilized to instruct his troops to come back and wall up themselves in the former presidios by abandoning their advanced positions. Thus, Spain cleared out and gave up to its international responsibilities and its national promises as well. Soon, the Slogan "Tanger per Espana" turned out to be "Morocco is a red iron that burns in our hands " as believed by an overwhelming majority of Spaniards in their complaints. Morocco became a cursed nation for Spain. Tangiers then remained for Spain, a "Nessus tunic" that it can’t willingly or whimsically get rid of. Besides, weakened as Spain was, it was constrained to accept and ratify the 1923 Convention which gave Tangiers an international dimension open to European economic and commercial liberalism. This marks the second humiliation of the Spanish people for Tangiers is both in hearts and minds, a Spanish land. This essay does not intend to revisit the Spanish colonial system in Morocco. It rather focuses on the history of the city of Tangiers, a geo-strategic site of fundamental importance in Mediterranean environment. It is the heart of international quarrels whose actors were Great Britain, France, Germany, Spain and to a lesser extent, Italy, Belgium, Holland and The United States of America.